Biofeedback - Schwartz, Mark (IntechOpen, 2018)
The six chapters in this volume form a timely introduction to biofeedback research. The six authors describe how objective electrophysiological data provides useful data for assessment and therapy for physical therapists, psychologists and other healthcare professionals and their clients. The first chapter, "Biofeedback and neurofeedback in the treatment of migraine", is written by Ph.D. student Zivoder Ivana. The second chapter by Prof. Dumitrascu looks at pelvic floor rehabilitation and is titled "Factors predicting failure in anorectal biofeedback". The third chapter by Dr Liao Da-Vin is titled "Collaborative, social-networked posture training with posturing monitoring and biofeedback". It is a useful and timely description of the role of biofeedback to support rehabilitation therapy at home and describe how objective information of physiotherapy treatments could increase the quality of service and the consistency of treatment outcomes. The fourth chapter by Prof. Silva Hugo is titled "Bridging the clinic-home divide in muscular rehabilitation". It also covers the role of biofeedback to support rehabilitation therapy at home. The fifth chapter is written by Ph.D. student Grin-Yatsenko Vera and is titled "Effect of infra-low frequency neurofeedback on infra-slow-EEG-fluctuations". The sixth and final chapter in the volume, "Control systems of bionic limbs of the new generation and control systems with EMG signals of VR and games, toys" by M.A. Ivaniuk Natallia goes beyond the person and shows how biofeedback can be integrated in the behavior of a bionic hand.